KAJIAN PERUBAHAN MUTU KUBIS (Brassica oleracea var gran 11) DALAM KEMASAN PLASTIK SELAMA PENYIMPANAN - Valentine Takaendengan; Ireine Longdong; Frans Wenur (Universitas Sam Ratulangi, 2015)
ABSTRACT The objective of this study were to obtain the appropriate packaging and storage temperature in extending the shelf life of cabbage and also to calculate weight loss and physical changes of cabbage (texture, color and the rate of CO2 production) during storage in the plastic packaging. The results showed that the cabbage stored at the temperature range from 5-10 °C using stretch film packaging gave the lowest shrinkage of 1.59% after being stored for 20 days. The cabbage packed with stretch film delivered the lowest production rate of CO2 that is 36.14 mg / jam.kg on the 1st day with a hardness value of cabbage at the top of 0.061 mm/g and at the base of 0.063 mm/g, and production rate of CO2 of 55.53 mg/jam.kg were obtained on the 20th day with the hardness at the top of the cabbage of 0.063 mm/g and at the base of 0.065 mm/g with the brightness level of 80.78 namely color level is white. Keywords: Cabbage, Packaging, Storage, Quality Change